2012
DOI: 10.1167/iovs.12-9874
|View full text |Cite
|
Sign up to set email alerts
|

A Genotype-Phenotype Comparison ofADAMTSL4andFBN1in Isolated Ectopia Lentis

Abstract: ADAMTSL4 is the most important known causative gene in isolated EL. Mutations in ADAMTSL4 appear to cause earlier manifestation of EL and are associated with increased axial length as compared to FBN1. We suggest that ADAMTSL4 be screened in all patients with isolated EL and that physicians be vigilant for the more severe ocular phenotype associated with mutations in this gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 42 publications
(58 reference statements)
7
63
1
4
Order By: Relevance
“…Specific ophthalmic features of the different conditions associated with EL have not been defined. Although superior movement of the crystalline lens has been suggested in MFS 13 and anterior dislocation in homocystinuria, 53 36 Greene et al (2010) 37 Aragon Martin et al (2010) 38 Neuhann et al (2010) 39 Chandra et al (2012) 40 Ectopia lentis et papillae (OMIM 225200)…”
Section: Other Autosomal Recessive Mutations Resulting In Elmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific ophthalmic features of the different conditions associated with EL have not been defined. Although superior movement of the crystalline lens has been suggested in MFS 13 and anterior dislocation in homocystinuria, 53 36 Greene et al (2010) 37 Aragon Martin et al (2010) 38 Neuhann et al (2010) 39 Chandra et al (2012) 40 Ectopia lentis et papillae (OMIM 225200)…”
Section: Other Autosomal Recessive Mutations Resulting In Elmentioning
confidence: 99%
“…Ahram and colleagues 36 19 years later described a homozygous nonsense mutation in ADAMTSL4 on 1q21.2 in the Jordanian family. Further mutations in this gene have been described causing autosomal recessive IEL [37][38][39][40] and ectopia lentis et pupillae (EL&P). [40][41][42] The genotype/ phenotype similarity of IEL and EL&P most likely represents a spectrum of anterior segment dysgenesis.…”
Section: Autosomal Recessive Ielmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously suggested that AL in isolated ectopia lentis may be influenced by causative genetic mutations (Chandra et al 2012). It would be of interest to know if this were also true with FBN1 mutations.…”
Section: Referencesmentioning
confidence: 97%
“…eir patients underwent detailed ocular, cardiovascular, skeletal examination and their ophthalmic features, including corneal problems, poor visual acuity, and direction of lens displacement, some of which we examined in our patient 2 . e condition can cause the aggressive secondary glaucoma that requires surgical treatment with lensectomy, vitrectomy, and drainage device implantation in order to avoid its devastating progression into glaucomatous optic atrophy 3 .…”
mentioning
confidence: 99%